CHRONIC COUGH (Homoeopathy for All, 2025)
Cough is a sudden and often repetitively occurring reflex that has been experienced by every human and is an essential protective and defensive act whose action secures the removal of mucus, noxious substances and infections from the larynx, trachea and larger bronchi. In addition to being an airway defence mechanism, coughing is a very common symptom observed in many diseases other than those affecting the respiratory system. Sometimes, impairment or absence of the coughing mechanism can be harmful and even fatal in disease.
Keywords: gastro oesophageal; morbidity; hypersensi tivity.; asthma/eosinophilic; oesophageal